Diferentes concepciones en los estudios de antropología urbana - Fernádez Álvarez, Óscar (Estudios humanísticos. Geografía, historia y arte, 1994)
A synthesis of the contributions and changes that have taken place in Urban Anthropology in this century is offered. In the 1960's reserches have expanded and become more complex in the question asked and the theorethical employed, reflecting both new insights and the changes that have ocurred in this discipline. Such research has now developed in many areas using various paradigms that we consider complementary, through we also note that changes are occurring in emphases. Our purpose in this paper is to illustrate, more than the past of the discipline, the worry for the future and the way to go ahead.